Relationship between phonological and geographical distance: Persian, Sarawani Balochi and Sistani dialect - Ahangar, Abbas Ali; Oostendorp, Marc van; Soohani, Bahareh (Penerbit UKM, 2013)
This article focuses on the study of geographical variations among the phonological systems of Standard Persian (SP) language, Central Sarawani Balochi (CSB), a dialect of Balochi language and the Sistani dialect (SD) of Persian, based on Optimality Theory (OT) and van Oostendorp‟s (2008) approach. SP and SD are linguistically closely related, but SP and CSB are very farther apart. While these language varieties share some similarities in their phonological system, they also have some peculiarities and are spoken in different geographical locations in Iran. Following OT and van Oostendorp‟s (2008) approach, the study of syllable structure of SP, CSB and SD supports the fact that the linguistic distance between two dialects is the minimal number of minimal reranking needed to get from one grammar to another. The findings of the present research show the fact that reranking DEP-IO and *COMPLEXONS constraints supports how the initial clusters are realized in the syllable structure of CSB and SD, but not in SP. In addition, the analysis of the status of [] in the onset position of the syllable structure of SP and SD based on the constraints: DEP-IO, ONSET and MAX-IO indicates that all these language varieties are among languages which typologically do not permit onset-less syllables. Moreover, the data suggests that the linguistic distance between two languages or dialects equals to the geographical distance between them. Further, as to syllable structure, historical considerations should be taken into account. Accordingly, the syllable structure of SD corresponds to the syllable structure of CSB rather than SP, although linguistically SD is closer to SP not CSB.